2000
DOI: 10.1016/s0002-9440(10)65042-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the ALK Tyrosine Kinase Gene in Neuroblastoma

Abstract: ALK (anaplastic lymphoma kinase) is a tyrosine kinase receptor, expressed as part of the chimeric NPM-ALK protein, in anaplastic large cell lymphomas (ALCLs) exhibiting the t(2;5)(p23;q35) translocation. As a result of this translocation, the NPM (nucleophosmin) gene is fused to the portion of the ALK gene encoding its intracytoplasmic segment. In normal mouse tissues, mRNA encoding the Alk receptor has been found only in neural cells, suggesting involvement of this receptor in the development of the nervous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
145
0
8

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(159 citation statements)
references
References 28 publications
6
145
0
8
Order By: Relevance
“…Five out of 8 cell lines exhibited high ALK expression, whereas 3 expressed only low levels. These results are consistent with previous reports which showed that full-length ALK is detected in almost half of the cell lines derived from neuroblastomas (33,34). We were unable to show that these patterns of expression were associated with ALK amplification and that there was an association between ALK and N-myc amplification.…”
Section: Discussionsupporting
confidence: 89%
“…Five out of 8 cell lines exhibited high ALK expression, whereas 3 expressed only low levels. These results are consistent with previous reports which showed that full-length ALK is detected in almost half of the cell lines derived from neuroblastomas (33,34). We were unable to show that these patterns of expression were associated with ALK amplification and that there was an association between ALK and N-myc amplification.…”
Section: Discussionsupporting
confidence: 89%
“…After a brief washing and subsequent incubation with the goatanti-mouse horseradish peroxidase-conjugated secondary antibody (Santa Cruz Biotechnology), the blots were developed by enhanced chemiluminescence reaction (ECL Detection reagents; GE Healthcare Global, Piscataway, NJ, USA). The human neuroblastoma cell line IMR32 30 with a recognized full-length ALK expression and normal kidney tissue were used as controls of ALK and VCL expression, respectively. Mouse monoclonal antib-actin primary antibody (Sigma-Aldrich) was used as the protein-loading control.…”
Section: Western Blottingmentioning
confidence: 99%
“…However, ALK was originally discovered when it was found that the chimeric N-terminal nucleophosmin (NPM) domain/cytoplasmic (catalytic) ALK domain fusion protein (NPM-ALK) is the oncoprotein underlying the pathogenesis of anaplastic large cell lymphomas (ALCL) [5,6]. NPM-ALK results from the (2;5) (p23;q35) chromosomal translocation, however, other translocations also lead to constitutive activation of ALK and other malignancies and furthermore, wild-type ALK has been postulated to be involved in the pathogenesis of rhabdomyosarcomas [7], neuroblastoma and neuroectodermal tumors [8,9], glioblastomas [10], and melanomas [11].…”
Section: Introductionmentioning
confidence: 99%